Pengembangan Sistem Reservasi Barbershop Berbasis Web Dan Mobile - Naja, Alfa Iqbal Ahlun; Fachrie, Muhammad; Handayani, Irma (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Arkan Barbershop is a barbershop located in the Wangon area of Banyumas Regency. Arkan Barbershop offers services such as haircuts, hair coloring, and other hair treatments. Currently, Arkan Barbershop still uses manual queues with numbers, resulting in customer congestion at certain times. This application is built using REST API and Laravel framework to process reservation data, services, and prices at Arkan Barbershop. Customers input the desired service and time to facilitate booking and to obtain information about the services available at the barbershop and the list of available service prices.